FATAL HEMORRHAGE DUE TO AORTIC RUPTURE IN AN OSTRICH (STRUTHIO CAMELUS) CHICK - R. Venkataramanan; S.T. Selvan; C. Sreekumar; P. Veeramani; H. Gopi; M. Babu (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The paper describes an incidence of aortic rupture in an ostrich chick maintained at the Post Graduate Research Institute in Animal Sciences, Kattupakkam. A male ostrich chick, aged 3 months died suddenly with bleeding from the mouth. A thorough necropsy was conducted. The carcass was pale. A blood clot of about 80 ml was noticed in the thoracic cavity adjacent to heart and it originated from a rupture in the aorta. The clot was found to extend into the neck around the trachea. Based on the necropsy lesions, it was concluded that death was due to oligaemic shock resulting from hemorrhage caused by ruptured aorta. Aortic rupture has been associated mainly with nutritional complications. Copper and zinc deficiencies, high protein or fat content in feed, degenerative changes in wall of aorta (atherosclerosis) and hypertension are some of the factors predisposing the condition. Nutritional changes such as increase in crude fiber, supplementation with reserpine and copper and decreasing the total energy and protein has given favourable results. It was concluded that the aortic rupture may be associated with nutritional complications.